Electrolyte Beverage Intake to Promote Hydration and Maintain Kidney Function in Guatemalan Sugarcane Workers Laboring in Hot Conditions. Issue 12 (December 2020) - Krisher, Lyndsay; Butler-Dawson, Jaime; Yoder, Hillary; Pilloni, Daniel; Dally, Miranda; Johnson, Evan C.; Jaramillo, Diana; Cruz, Alex; Asensio, Claudia; Newman, Lee S.
Abstract : Objectives: To evaluate impact of electrolyte supplementation on hydration status and health outcomes in Guatemalan agricultural workers performing heavy work under hot climatic conditions. Methods: A 3-week pragmatic trial was conducted with a group of 50 workers during the 2017 to 2018 sugarcane harvest. Workers received an electrolyte hydration intervention during 2 of the 3 weeks. Blood and urine samples were collected each week. Results: Increased electrolyte intake resulted in less muscle injury. Kidney function was maintained across the intervention period. Workers were adequately hydrated and average electrolyte levels remained in normal ranges. Mild indications of hyponatremia occurred at higher levels of fluid intake. Conclusions: This trial demonstrates the feasibility of maintaining workers' electrolyte levels under extremely hot and humid conditions while mitigating muscle injury. Electrolyte supplementation should be added to standard workplace water, rest, and shade interventions to protect workers. Abstract : Supplemental Digital Content is available in the text